A new biogeographically disjunct giant gecko (Gehyra: Gekkonidae: Reptilia) from the East Melanesian Islands - Oliver, Paul M.; Clegg, Jonathan R.; Fisher, Robert N.; Richards, Stephen J.; Taylor, Peter N.; Jocque, Merlijn M. T. (Zootaxa, 2016)
The East Melanesian Islands have been a focal area for research into island biogeography and community ecology. However, previously undescribed and biogeographically significant new species endemic to this region continue to be discovered. Here we describe a phylogenetically distinct (~20% divergence at the mitochondrial ND2 gene) and biogeographically disjunct new species of gecko in the genus Gehyra, from the Admiralty and St Matthias Islands. Gehyra rohan sp. nov. can be distinguished from all congeners by the combination of its very large size, ring of bright orange scales around the eye, moderate degree of lateral folding on the limbs and body, and aspects of head, body and tail scalation. Molecular data indicate mid to late Miocene divergence of the new species from nearest relatives occurring nearly 2000 kilometres away in Vanuatu and Fiji. Large Gehyra have not been recorded on the intervening large islands of the Bismark Archipelago (New Britain and New Ireland) and the Solomon Islands, suggesting this dispersal pre-dated the current configuration of these islands, extinction in intervening regions, or potentially elements of both. Conversely, low genetic divergence between disjunct samples on Manus and Mussau implies recent overseas dispersal via either natural or anthropogenic means.